Analysis of Elementary School-Age Children’s Development and Its Implications for the Learning Process - Khairunnisa, Khairunnisa; Hasby, M.; Harto, Kasinyo; Suryana, Ermis (Journal of Social Work and Science Education, 2025)
This study analyzes the development of elementary school-aged children at SDN 55 Palembang and its implications for the learning process. Using qualitative methods (observation, interviews, and documentation), this study reveals variations in children’s cognitive, affective, and psychomotor development. Most children, according to Piaget’s theory, are at the concrete operational stage, showing the ability to think logically about concrete objects but are limited to abstract reasoning. This variation in development is influenced by internal factors (talent, interest, motivation) and external factors (family environment, parental support, access to learning resources). Differences in development have implications for the need for differentiated learning strategies. The study recommends an inclusive and responsive learning approach to individual needs, emphasizing collaboration between teachers, parents, and the community in creating an optimal learning environment. The need for training for teachers to understand and apply teaching methods that are appropriate to the characteristics of children’s development is also proposed, so that each student can reach their maximum potential.